Sistem Pendeteksi Gelombang Otak Berbasis Electroencephalogram (EEG) Pada Penderita Alzheimer - Kurnia Alfikri; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The brain controls our thoughts, memory and speech, movement of the arms and legs, and the function of many organs within our body. If someone has a healthy brain, then will encourage physical health. In the other way around, if the person brain is in an unhealthy condition, then that is the cause of all problems in the body. Some doctors use a device called an electroencephalogram (EEG) to diagnose the brain in humans. Electroencephalogram (EEG) is a medical test used to measure the electrical activity of the brain. EEG is done by placing electrodes on the scalp. EEG is often also referred to as a brain wave test. The EEG procedure is not painful and can be done without having to shave hair. EEG will help diagnose a number of health conditions such as Alzheimer's disease. The method used is to measure human brain waves using the designed EEG device. EEG signal output using MATLAB software. This study aims to design an EEG system to diagnose Alzheimer's disease and display the results of EEG signal readings in MATLAB. Keywords: EEG, MATLAB, Alzheimer, Brain.